ANALISIS POTENSI WILAYAH KOMODITAS TANAMAN PANGAN DAN HORTIKULTURA DI KABUPATEN KENDAL - Mandamdari, Alpha Nadeira; Elyanto, Adwi Herry Koesoema; Widjojoko, Tatang (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
Kendal is one of the regencies in Central Java province that has great agricultural potential. The large potential of the agricultural sector can be developed towards food security by developing site-specific agricultural sub-sectors in each sub-district in Kendal district. Therefore, it is necessary to identify the potential of the agricultural sub-sector through the determination of basic plant commodities. The results showed that Kendal district has 8 basic food crops and 10 basic horticultural crops. The basic commodities cultivated in most sub-districts are lowland rice, corn and cassava; cayenne pepper, large chili and shallot; and mango and banana. These basic commodities have fast growth, competitive advantages and are classified as superior which can be a priority to be developed in Kendal district.